2018
DOI: 10.1111/hae.13467
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of passive musculoarticular ankle stiffness in children, adolescents and young adults with haemophilic ankle arthropathy

Abstract: This study confirmed increased ES in the severely affected ankles of CAAwH compared to non-affected sides. No differences in the ankle viscoelastic properties of CAAwH with or without joint damage were observed, however, compared to matched TDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Our results showed excellent intra-and interoperator reliability of the EOD in healthy participants of 5 to 90 years old. Lobet et al (2018) showed comparable results in their study on the ankle, with good-to-excellent intra-and interday reliability in PMAS of the ankle in children, adolescents, and adults with hemophilia using the same assessment protocol. The reliability study showed that EOD might not be as accurate with the standard error of the mean (SEM) around 10% and MDC of 25%; this might be related to excessive forearm movement into the cast during the acquisitions at high frequencies or non-linear soft tissue behavior at high frequencies and should continue to be investigated.…”
Section: Reliabilitymentioning
confidence: 76%
“…Our results showed excellent intra-and interoperator reliability of the EOD in healthy participants of 5 to 90 years old. Lobet et al (2018) showed comparable results in their study on the ankle, with good-to-excellent intra-and interday reliability in PMAS of the ankle in children, adolescents, and adults with hemophilia using the same assessment protocol. The reliability study showed that EOD might not be as accurate with the standard error of the mean (SEM) around 10% and MDC of 25%; this might be related to excessive forearm movement into the cast during the acquisitions at high frequencies or non-linear soft tissue behavior at high frequencies and should continue to be investigated.…”
Section: Reliabilitymentioning
confidence: 76%
“…In the lower limb, haemophilic arthropathy commonly affects the range of motion of the knee and ankle joints and has also an impact on muscle size, muscle force capacity and proprioception . While the interest in the musculoskeletal properties and biomechanics of movement of people with haemophilic arthropathy (PWHA) has recently increased, the effects of haemophilic arthropathy on neuromuscular control during gait have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were not confirmed in a more recent study by Lobet et al (2017) who found that children and adolescents with haemophilic arthropathy are functionally less disabled than structural evaluations would suggest, contrarily to adult patients, 8 who present progressive quadriceps weakness with increasing age stages, as compared to healthy individuals 9 . More recently, Lobet et al 10 studied the effect of structural joint damage on the elastic stiffness of the ankle in CwH and highlighted that the latter was significantly increased in children and adults with unilateral affected ankle joints compared to the non‐affected side. The same research group also observed a poorer postural control in this young study population, suggesting that a complex pathophysiological and neurophysiological modulation is initiated by chronic bleedings, which may originate both from unilateral and bilateral deterioration of the musculoskeletal system 11 .…”
Section: Introductionmentioning
confidence: 85%